Dominant influenza A(H3N2) and B/Yamagata virus circulation in EU/EEA, 2016/17 and 2017/18 seasons, respectively - Adlhoch, Cornelia (2018)
Members of the European Influenza Surveillance Network: Portugal (Figueiredo Augusto Gonçalo, Machado Jorge, Moreira Guiomar Raquel, Nogueira Paulo, Rebelo de Andrade Helena, Rodrigues Ana Paula)